2015
DOI: 10.1093/infdis/jiv297
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Origins of theSalmonellaBareilly Strain Causing a Food-borne Outbreak in the United States

Abstract: These data represent the first report fully integrating WGS analysis with geographic mapping and a novel use of transmission networks. Results showed that WGS vastly improves our ability to delimit the scope and source of bacterial food-borne contamination events. Furthermore, these findings reinforce the extraordinary utility that WGS brings to global outbreak investigation as a greatly enhanced approach to protecting the human food supply chain as well as public health in general.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
122
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(127 citation statements)
references
References 22 publications
3
122
0
2
Order By: Relevance
“…The first case study used whole genome read data from ten Salmonella enterica sequences associated with a 2010 outbreak, and the observed phylogeny inferred from those data [2]. We used a completed Salmonella enterica genome (CFSAN000189, GenBank: CP006053.1) as the anchor sequence, and simulated 200 variable sites under the generalized time reversible (GTR) model at an average coverage of 20 reads per site.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first case study used whole genome read data from ten Salmonella enterica sequences associated with a 2010 outbreak, and the observed phylogeny inferred from those data [2]. We used a completed Salmonella enterica genome (CFSAN000189, GenBank: CP006053.1) as the anchor sequence, and simulated 200 variable sites under the generalized time reversible (GTR) model at an average coverage of 20 reads per site.…”
Section: Resultsmentioning
confidence: 99%
“…However, these estimates of shared ancestry may rely on only a handful of data points. When the resulting phylogenetic trees are used by public health agencies to make public health decisions, such as to define the scope of foodborne outbreaks [1], to identify the source of these outbreaks [2][3][4] and where appropriate to follow-up with *Correspondence: ejmctavish@ucmerced.edu 1 University of California, Merced, Merced, CA, USA Full list of author information is available at the end of the article regulatory or legal actions, it is particularly important to ensure that the WGS analysis methods used are validated.…”
Section: Introductionmentioning
confidence: 99%
“…The idea that geographic source attribution could be successful came in 2012 during retrospective WGS. In that study, a Salmonella Bareilly outbreak in the United States was successfully linked by WGS to a scraped tuna product imported from India on the basis of sequence similarity to a 5-year-old historical isolate from the FDA archives that was collected from a processing facility Ͻ8 km away from the source of the 2012 outbreak (182). In addition to this initial observation, later studies have shown that geographic source attribution can be useful as a tool for delineating geographically dispersed outbreaks.…”
Section: Geographic Source Attributionmentioning
confidence: 99%
“…The fact that this bacterium survives in soil and water and may be transfered to fish plays an important role in providing information on the nature of the contamination and the possible dissemination route of this bacterium, thus allowing traceability of the microbial source in fish slaughterhouses (SETTI et al, 2009;HOFFMANN et al, 2016).…”
Section: Introductionmentioning
confidence: 99%